Teaching Christology in Light of Feminist Issues - Kopas, Jane (Horizons, 1986)
While awareness of feminist issues has not left its mark on all professors of theology, much less on all who teach christology, those whose awareness has been changed by facing these issues often find themselves asking how they can bring them to bear on courses with already substantial content. The point of raising feminist issues, however, is not a matter of adding content but of uncovering questions that have not been asked and of transforming the way we look at key areas of the discipline. This is turn leads to the discovery of new resources and new insights.My own approach in teaching "Christ in Tradition and Culture" to undergraduates has been to uncover feminist issues and concerns that are in the mainstream of christology. I have done this by looking at scriptural, theological, and soteriological/spiritual perspectives that are central to the development of a contemporary christology. The purpose of this article is to share the ways I deal with feminist issues within the perspectives noted and to indicate some of the more important bibliographic resources that address them. Before examining issues that surface in the various perspectives, it may be helpful to underscore some aspects of feminist theology that should be kept in mind.